Relationship of Age with the Event of Chronic Energy Lack For Pregnant Mothers - Ike Trinadewi Wahyuni; Mariyani Mariyani (Pusat Riset dan Inovasi Nasional, 2022)
Background : According to WHO, every day in 2019 around 810 women died, by the end of the year 295,000 people from 94% of them were in developing countries. The direct cause of maternal death by 90% are complications that occur during delivery and after delivery. Chronic Energy Deficiency is a condition caused by an imbalance in nutritional intake between energy and protein, so that the nutrients needed by the body are not fulfilled. Based on the results of the Nutrition Status Monitoring in 2017, it was found that the percentage of pregnant women with chronic energy deficiency in Indonesia was 14.8%. The prevalence of CED in pregnant women in Indonesia based on Riskesdas data in 2018 is 17.3% and based on the Indonesian Health profile that the incidence of CED in pregnant women in 2019 is 17.9% Objective : Knowing the relationship between age and the incidence of chronic energy deficiency (KEK) in pregnant women Methods : Analytical with cross sectional approach. The sample in this study were all maternity mothers registered in the register from March 2021 to May 2022 as many as 224 people (total sampling). Results : The distribution of the frequency of CED incidence in pregnant women is 366.6%. Age of pregnant women mostly aged 20-35 years 69.2%, LBW 3.6% and 3.1% bleeding. There is a significant relationship between age and the incidence of CED in pregnant women with a p value of 0.000. Conclusions and Suggestions: There is a significant relationship between age and the incidence of CED in pregnant women. It is expected that health workers, especially midwives, provide counseling to pregnant women about nutritional needs during pregnancy.